Broad fibrovascular cores may not be an exclusively benign feature in papillary lesions of the breast: a cautionary note. Issue 3 (23rd September 2013) - Yamaguchi, Rin; Tanaka, Maki; Tse, Gary M; Yamaguchi, Miki; Terasaki, Hiroshi; Nomura, Yoriko; Takenaka, Miki; Naito, Yoshiki; Akiba, Jun; Yano, Hirohisa
Abstract : Aims: A prominent fibrovascular stromal core is one of the widely accepted histological features of breast papillomas, but some papillary carcinomas also show such broad fibrovascular cores, leading to confusion in diagnosis, particularly in needle biopsy specimens. We investigated the histological characteristics of papillary lesions, focusing on broad fibrovascular cores and their relationship with the architectural patterns. Methods: Among 185 cases of needle biopsies of papillomas and papillary carcinomas, the number of cases with broad fibrovascular cores in each group was compared. The broad fibrovascular core density in the subsequently resected specimens was evaluated and compared between papillary predominant pattern (papillary structures >80% of tumours) and mixed pattern (papillary, solid, cribriform and others) within the lesions. Results: Significantly more papillary carcinomas than papillomas and B3 atypical papillary lesions had broad fibrovascular cores (p=0.0091 and p=0.0164, respectively). The papillary predominant pattern was more prominent in carcinomas than in papillomas in the needle biopsies (p=0.048) and showed the same tendency in the resections (p=0.058). The broad fibrovascular core density was significantly lower in the 18 papillomas than in the 37 papillary carcinomas (p=0.0079) and was not significantly different between the papillary predominant and mixed patterns in carcinomas and papillomas. Conclusions: Broad fibrovascular cores in mammary papillary lesions are not specific for papillomas, as they are also present focally in papillary carcinomas. As the frequency of papillary carcinoma with broad fibrovascular cores is relatively high, caution in diagnosis has to be exercised, especially in needle biopsy specimens.